Avaliação da folha de moringa (moringa oleifera) na alimentação e imunidade de codornas europeias (coturnix coturnix) - Macchi, Paloma de Matos (Universidade Federal Rural do Semi-Árido, 2020)
Moringa oleifera is a plant that has shown important nutritional and functional characteristics in animal feed. This study aimed to evaluate the effect of including Moringa oleifera leaf in the feeding of European quails (Coturnix coturnix) on parameters of zootechnical performance, carcass yield, weight of organs and serum biochemistry, aiming to improve immunological conditions, mitigating factors such as stress caused by environmental heat, in addition to reducing food costs without compromising welfare. A total of 360 mixed European quails from Granja Fujikura® were used, aged 1 to 42 days, randomly distributed into 05 groups, which consisted of 05 treatments (06 subgroups), with n = 12. The birds were fed ad libitum with experimental diets containing 05 levels (0, 1, 2, 3 and 4%) of protein inclusion of Moringa oleifera leaves in replacement of corn protein and soybean meal (FMO). The zootechnical performance was evaluated in two phases (1 to 21 days and 22 to 42 days of age). For carcass evaluation, samples of 02 birds per experimental subgroup were slaughtered at 28, 35 and 42 days of age. The sampling of blood and organs occurred at 14, 28 and 42 days of age, from 01 bird per subgroup, sacrificed for evaluation of serum biochemistry (Aspartate aminotransferase (AST); Alanine aminotransferase (ALT); Alkaline phosphatase (ALP); Cholesterol; Triglycerides; Glucose) and weight of immune and edible organs. The results of performance, carcass yield, organ weight and blood parameters were submitted to ANOVA and polynomial regression or factorial scheme. When there was an interaction of the analyzed factors, Tukey's test was performed at 5% significance level. In the experimental conditions, the results showed that FMO up to the level of 2.24% in the period from 1 to 42 days of age of European quails, or up to 2.61% in the period of 22 to 42 days of age, did not interfere in the productive performance. Up to the 4% level of FMO, there was no influence on the carcass yield of females slaughtered at 28, 35 and 42 days of age. However, increasing the FMO inclusion to 4% reduced the carcass yield of males slaughtered at 35 days of age who, regardless of the FMO level, do not gain weight after this age. The inclusion of 4% of FMO decreased the weight of the European quail cloacal pouch at 14 days of age, causing an increase in the weight of the thymus and a reduction in the spleen at 42 days. There was no interference in glucose and triglyceride levels at 14, 28 and 42 days of age. The inclusion of FMO reduced cholesterol at 14 days, suggesting that during this period there was poor digestion and absorption of nutrients. The levels of AST, ALT and ALP were within the normal range for birds at all levels of inclusion of FMO, however up to 3.03% of FMO caused an increase in ALT while up to the 2.26% level there was a reduction in ALP. FMO levels up to 4% proved to be economically viable, considering only the cost of feeding mixed European quails at 28, 35 and 42 days of age, but there was a tendency to reduce economic viability with increasing age. The inclusion of 3% of FMO demonstrated better economic viability, the use being conditioned to availability and cost in the region.
Keywords: Carcaça; Bioquímica sérica; Estresse térmico; Análise econômica; Carcass yield; Serum biochemistry; Thermal stress; Economic analysis; CIENCIAS AGRARIAS::MEDICINA VETERINARIA